Lipoteichoic acid from Bacillus subtilis subsp. niger WM: isolation and effects on cell wall autolysis and turnover. - Meyer, P D (1987)
Lipoteichoic acid (LTA) was extracted by means of hot aqueous phenol from Bacillus subtilis subsp. niger WM cells grown under various conditions in chemostat culture. The extracts were partially purified by nuclease treatment and gel permeation chromatography. Chemical analyses revealed a composition consistent with a polyglycerol phosphate polymer. The influence on autolysis of the LTAs thus obtained was studied with both whole cells and autolysin-containing native walls of B. subtilis subsp. niger WM. Lysis rates of phosphate-limited cells could be reduced to about 40% of the control rate by the addition of LTA, whereas lysis of cells grown under phosphate-sufficient conditions was affected to a much lesser extent. The lysis of native walls prepared from variously grown cells proved to be fairly insensitive to the addition of LTA. The effect of LTA on wall turnover was studied by following the release of radioactively labeled wall material during exponential growth. The most obvious effect of LTA was a lowered first-order rate of release of labeled wall material; calculations according to the model for cell wall turnover in Bacillus spp. formulated by De Boer et al. (W. R. De Boer, F. J. Kruyssen, and J. T. M. Wouters, J. Bacteriol. 145:50-60, 1981) revealed changes in wall geometry and not in turnover rate in the presence of LTA.